Recognizing Florida's Venomous Snakes - Steve A. Johnson; Martin B. Main (EDIS)
Florida is home to 45 species of native snakes, six of which are venomous (poisonous). The venomous species include five pit vipers (Eastern Diamond-backed Rattlesnake, Timber Rattlesnake, Pygmy Rattlesnake, Copperhead, and Cottonmouth) and the Coral Snake. Although each of the six venomous species in Florida have unique characteristics that allow them to be readily identified by experts, there are many non-venomous species with which the venomous species may be confused. Therefore it is best not to attempt to capture, harass, or harm any snake. To do so may put you at risk of being bitten by a venomous species. This document is WEC 202, one of a 4-part series of the Department of Wildlife Ecology and Conservation entitled Dealing with Venomous Snakes in Florida School Yards, UF/IFAS Extension. Original publication date September 2005.